Preliminary geothermal investigations at Manley Hot Springs, Alaska - East, Jennifer (University of Alaska Fairbanks. Geophysical Institute., 1982)
Manley Hot Springs is one of several hot springs which form a belt extending from the Seward Peninsula to east-central Alaska. All of the hot springs are low-temperature, water-dominated geothermal systems, having formed as the result of circulation of meteoric water along deepseated fractures near or within granitic intrusives. Shallow, thermally disturbed ground at Manley Hot Springs constitutes an area of 1.2 km by 0.6 km along the lower slopes of Bean Ridge on the north side of the Tanana Valley. This area includes 32 springs and seeps and one warm (29.1/sup 0/C) well. The hottest springs range in temperature from 61/sup 0/ to 47/sup 0/C and are presently utilized for space heating and irrigation. This study was designed to characterize the geothermal system present at Manley Hot Springs and delineate likely sites for geothermal drilling. Several surveys were conducted over a grid system which included shallow ground temperature, helium soil gas, mercury soil and resistivity surveys. In addition, a reconnaissance ground temperature survey and water chemistry sampling program was undertaken. The preliminary results, including some preliminary water chemistry, show that shallow hydrothermal activity can be delineated by many of the surveys. Three localities are targeted as likely geothermal well sites, and a model is proposed for the geothermal system at Manley Hot Springs.